(untitled) (Journal of actual problems of jurisprudence, 2019)
One of the modern phenomena that has had a major impact on the development of global processes in the global community was the intensification of information and communication technologies. The scale of cultural, social, economic, political, and legal changes arising from the spread of networked computer communications allows many scholars to consider them as the beginning of a new era in the history of human civilization. It is no secret that the use of the global computer network is one of the most important prerequisites for globalization and the creation of an information society. As we have already noted, cybercrime is a cybercrime crime that is aimed at cybercrime-based tools and devices that are used to break various social relationships protected by law and telecommunications networks. Cybercrime has such signs as lawlessness, social danger, guilt and punishment. The study of the characteristics and features of cybercrime often causes certain difficulties. First, the lack of a terminological apparatus established for this group of unlawful actions in judicial practice and law enforcement practice. The subject of criminal offenses is the information provided by law and contained in the electronic media; information systems, including information systems of state bodies; telecommunication network; state electronic information resources. Key words: cybercrime, crime, globalization, cybercrime, criminal code.